Whole-genome characterization of G12 rotavirus strains detected in Mozambique reveals a co-infection with a GXP[14] strain of possible animal origin. (29th May 2019) - Strydom, Amy; Motanyane, Lithabiso; Nyaga, Martin M.; João, Eva Dora; Cuamba, Assa; Mandomando, Inácio; Cassocera, Marta; de Deus, Nilsa; O'Neill, Hester
Abstract : A high prevalence of G12 rotavirus strains has previously been reported in southern Mozambique. In this study, the full genomes of five Mozambican G12 strains were determined directly from stool using an Illumina Miseq platform. One sample (0060) contained an intergenogroup co-infection of a G12P[8] Wa-like strain and a GXP[14] DS-1-like strain. The sequences of seven genome segments, detected for the GXP[14] strain, clustered with a diverse group of mostly animal strains, suggesting co-infection with a strain of possible animal origin. The stool samples contained G12P[6] rotavirus strains with Wa-like backbones. Phylogenetic analyses of the VP4 and VP7 encoding segments of the G12P[6] strains suggested that they were reassortants containing backbones that are similar to that of the G12P[8] strain. The study confirms previous observations of interspecies transmission and emphasizes the importance of whole-genome sequencing in order to evaluate rotavirus co-infections and reassortants.